Perspektif Madzhab Syafi’i Terkait Jual Beli Online - Fawaid Fawaid (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Online buying and selling is a buying and selling practice that makes it very easy for both parties to carry out transactions, this is because online buying and selling transactions can be carried out without face to face. But often this convenience is utilized by irresponsible parties, so that it can harm other parties. Nevertheless, online buying and selling is very popular and has become a habit in shopping by the Indonesian people. So in this study, researchers used the perspective of the Shafi'i madzhab in examining the law of online buying and selling.